An SDN-Based Approach to Ward Off LAN Attacks - Rietz, René; Cwalinski, Radoslaw; König, Hartmut; Brinner, Andreas (Journal of Computer Networks and Communications, 2018)
The detection of attacks on large administrative network domains is nowadays generally accomplished centrally by analyzing the data traffic on the uplink to the Internet. The first phase of an infection is usually difficult to observe. Often attackers use e-mail attachments or external media, such as USB sticks, hardware with preinstalled malware, or contaminated mobile devices to infect target systems. In such scenarios, the initial infection cannot be blocked at the network level. The lateral movement of attack programs (exploits) through internal networks and the exfiltration of data, however, which are the main purpose of targeted attacks, run always over the network. Security measures against such internal network attacks require a comprehensive monitoring concept that spans the entire network to its edge. Especially for preventive measures, this means providing a security concept for local area networks (LANs). In this paper, we propose based on an analysis of typical LAN-based attacks an approach for preventing these attacks for both IPv4 and IPv6 networks. It applies the software-defined networking (SDN) paradigm for centralizing the related network decisions in a central authority—the SDN controller—that manages all network connections and hence the associated data flows.